The perfect poison - Quick, Amanda (Detroit [Mich.] : Thorndike Press, 2009)
Plagued by rumors that she poisoned her fiancé, Lucinda Bromley manages to live on the fringes of polite society. She tends her beloved plants and occasionally consults on a murder investigation, for the notorious botanist can detect almost any type of poison. But the murder of a lord has Lucinda shaken. She has detected a poison containing a very rare species of fern. So rare that the only specimen in England was in her conservatory - until it was stolen last month.
"Thorndike Press large print basic"--t.p. verso.
Originally published: G.P. Putnam's Sons, 2009.
Keywords: Women botanists -- England -- Fiction; Secret societies -- England -- Fiction; Psychic ability -- Fiction; Murder -- Investigation -- Fiction; Large type books; Mystery fiction; Romantic suspense fiction